Dıgıtal transformatıon ın healthcare: global best practıces and Kazakhstan’s path forward - Ainur B. Qumar; Kamila Faizullina; Laura Seiduanova; Ayaulym Yelibay; Nurila Zhamankulova; Nurzhan Mukashev (Central Asian Journal of Medical Hypotheses and Ethics, 2025)
Digital transformation of healthcare is a global priority driven by technological innovation, patient-centered care, and increasing demands for efficiency. This article reviews international best practices in digital healthcare systems, assesses the current state of healthcare digitalization in Kazakhstan, and explores opportunities to adopt successful global strategies. It also highlights ongoing challenges, including fragmentation of digital systems, lack of interoperability, and disparities in access to healthcare between urban and rural areas. Policy recommendations for Kazakhstan based on international experience are provided. These include developing a unified national digital healthcare platform, enhancing cybersecurity and interoperability standards, expanding telemedicine, and investing in digital literacy and workforce training. Adopting a patient-centered, innovative approach will be critical to aligning Kazakhstan’s healthcare system with global best practices.